2013
DOI: 10.1007/s00520-013-1978-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of lipopolysaccharide-binding protein for predicting bacteremia/clinical sepsis in children with febrile neutropenia: comparison with interleukin-6, procalcitonin, and C-reactive protein

Abstract: On admission and 24 h later, the LBP concentration is less accurate for predicting bacteremia/clinical sepsis compared to IL-6, PCT, and CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 43 publications
2
42
0
3
Order By: Relevance
“…Procalcitonin is another parameter of infection that showed a significant increase (p<0.001) in FS patients compared with that of the control group (Table 1), that has been discussed previously (24).PCT increases in bacterial infection and is an accurate predictor of a serious bacterial infection (12,25).…”
Section: Discussion Comparison Between Fs Patients and Control Groupssupporting
confidence: 54%
See 1 more Smart Citation
“…Procalcitonin is another parameter of infection that showed a significant increase (p<0.001) in FS patients compared with that of the control group (Table 1), that has been discussed previously (24).PCT increases in bacterial infection and is an accurate predictor of a serious bacterial infection (12,25).…”
Section: Discussion Comparison Between Fs Patients and Control Groupssupporting
confidence: 54%
“…Presently, some physician use PCT to differentiate FS patients with bacterial and nonbacterial infectious causes (12).…”
Section: Introductionmentioning
confidence: 99%
“…CRP is a useful marker of the severity of an infection, and resistin may function similarly as a prognostic factor. Previous studies have reported that resistin may indicate the severity of the disease in patients with neonatal sepsis, in a similar manner to IL-6 and CRP (7,14,23,24). Furthermore, recent studies have demonstrated that resistin may serve a function in inflammation and autoimmunity (5,25).…”
Section: Discussionmentioning
confidence: 89%
“…However, using the CRP response as a biomarker for cellulitis has a number of disadvantages, including a delayed release and low specificity. Thus, numerous biomarkers, including resistin, have been studied in association with infectious diseases (8,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 has been shown to be a sensitive biomarker for predicting bacteremia/clinical sepsis in children with febrile neutropenia [45,46]. In severe sepsis, the best diagnostic accuracies were found for I-6 and procalcitonin and these were significantly higher than those for Lipopolysaccharide-Binding Protein (LBP) on admission [46].…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%